A STUDY ON LEARNING HABITS AND ACADEMIC ADJUSTMENT OF SECONDARY STUDENTS OF GOVERNMENT AND PRIVATE SCHOOLS IN FARIDABAD (Lex localis - Journal of Local Self-Government, 2025)
The present study investigates the relationship between learning habits and academic adjustment among secondary school students in Faridabad, with a particular emphasis on comparing learners from government and private institutions. Secondary education, especially at the Class 10 level, represents a transitional stage where students face heightened academic pressures and developmental challenges that demand both effective study practices and adaptive coping strategies. Recognizing this, the study was designed to examine how institutional context influences students’ ability to cultivate regular study routines and adjust to academic demands. A purposive sample of 100 students was selected, comprising 50 students from government schools and 50 students from private schools. Data were collected through the administration of a standardized Study Habits Inventory and an Adjustment Inventory for School Students, complemented by self-developed items to capture context-specific details. Statistical analyses, including mean, standard deviation, and t-tests, were employed to compare the two groups. The findings revealed significant differences in both dimensions. Private school students displayed more systematic study habits, characterized by regular planning, effective time management, and consistent revision practices. In contrast, government school students demonstrated stronger academic adjustment, particularly in adapting to classroom environments, managing peer influences, and coping with examination stress. These results suggest that while institutional resources and parental involvement may support the development of disciplined study habits in private schools, the diverse challenges faced by government school students foster resilience and adaptability. The study concludes that both school types nurture distinct strengths, which, if integrated, can produce more holistic student development. It shows the need for targeted interventions such as study skills workshops in government schools and counseling or peer-support programs in private schools to balance study habits with adjustment abilities. The research not only contributes to the comparative literature on secondary education but also offers practical insights for teachers, parents, and policymakers seeking to enhance learning outcomes and student well-being in diverse schooling contexts.